Internationalisation in Vietnamese Higher Education (Cham : Springer International Publishing, 2018)
This book focuses on models, strengths, opportunities, constraints and tensions in internationalisation in Vietnamese higher education. It reflects on key concepts from contemporary theories and models of internationalisation and discusses the implications for innovation, flexibility and responsiveness to local needs in Vietnam. Based on empirical research, theoretical knowledge and the experiences of researchers from Vietnam and overseas, the book draws out the distinctiveness and complexity of internationalisation practices and charts a way forward. It examines the key drivers and dimensions of internationalising Vietnamese higher education, and compares internationalisation in Vietnam to that in other countries. It clarifies and discusses tensions related to the appropriation of 'Western' internationalisation practice and models, and neo-liberal ideologies, to the local context of Vietnam. It provides readers with insights into government policy, quality assurance and benchmarking strategies, curriculum, the impact of international organisations on higher education, international student mobility, transnational education, employability, brain drain and brain gain and brain circulation.
1. Introduction: Internationalisation of Vietnamese higher education: An overview; Ly Thi Tran and Simon Marginson -- PART 1. POLICY AND PRACTICE IN INTERNATIONALISATION -- 2. Vietnam's government policies and practices in Internationalisation of higher education; Lan Hoang, Ly Thi Tran and Hiep-Hung Pham -- 3. Current perspectives on internationalisation of quality assurance at the institutional level; Quyen T. N. Do -- 4. The 'Advanced Programmes' in Vietnam: Internationalising the curriculum or importing the 'Best Curriculum' of the West?; Ly Thi Tran, Huong Le Thanh Phan and Simon Marginson -- 5. Transnational education in the Vietnamese market: Paradoxes and possibilities; Nhai Nguyen -- 6. Impacts of international organizations on Vietnam's higher education policy: The good, the bad and the ugly; Diep N. Tran -- 7. English-medium-instruction management: The missing piece in the internationalisation puzzle of Vietnamese higher education; Thu Nguyen -- PART 2. STUDENT MOBILITY, EMPLOYABILITY AND CONTRIBUTIONS -- 8. Historical trends of Vietnamese international student mobility; Chi Hong Nguyen -- 9. International students' choice of destinations for overseas study: A specific push-pull model for Vietnam; Hiep-Hung Pham -- 10. International students' aspiration to contribute to socioeconomic development in Vietnam; Lien Pham -- 11. Employers' perspectives on Vietnamese returnee students; Anh Pham -- 12. From brain drain and brain grain to brain circulation: Conceptualizing re-expatriation intentions of Vietnamese returnees; Nga Thi Thuy Ho, Pi-Shen Seet and Janice Jones -- 13. Vietnamese students' transition to international non-government organisations; Lan Thi Quynh Mai -- 14. Conclusion; Ly Thi Tran and Simon Marginson. .
Education
text file PDF
Keywords: International education .; Comparative education; Higher education; Educational policy; Education and state